How to Use Nebulized Antibiotics in Severe Respiratory Infections - Julie Gorham; Fabio S. Taccone; Maya Hites (MDPI AG, 2023)
Difficult-to-treat pulmonary infections caused by multidrug-resistant (MDR) pathogens are of great concern because their incidence continues to increase worldwide and they are associated with high morbidity and mortality. Nebulized antibiotics are increasingly being used in this context. The advantages of the administration of a nebulized antibiotic in respiratory tract infections due to MDR include the potential to deliver higher drug concentrations to the site of infection, thus minimizing the systemic adverse effects observed with the use of parenteral or oral antibiotic agents. However, there is an inconsistency between the large amount of experimental evidence supporting the administration of nebulized antibiotics and the paucity of clinical studies confirming the efficacy and safety of these drugs. In this narrative review, we describe the current evidence on the use of nebulized antibiotics for the treatment of severe respiratory infections.